Peran Zakat, Infaq dan Sedekah (ZIS) dalam Peningkatan Kesejahteraan Ekonomi Masyarakat: Studi pada LAZISNU Kecamatan Cluring - Ma’rifatul Munawaroh (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This study aims to describe the role of LAZISNU in distributing ZIS funds to Mustahik and describe the impact of ZIS on improving the economic welfare of the community. The research method applied in this study is qualitative research. There are three data collection techniques used, namely observation, interviews, and documentation. Data analysis using interactive analysis includes data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that LAZISNU in distributing ZIS funds Cluring District show that LAZISNU has succeeded in identifying and mapping Mustahik accurately and implementing a transparent and accountable distribution mechanism. Through programs that are not only consumptive but also economic empowerment, LAZISNU is able to provide a significant positive impact on improving community welfare. Although challenges in increasing public awareness still exist, the effectiveness and sustainability of the ZIS program run by LAZISNU provide hope for poverty alleviation and economic development in Cluring District.